Myth of A-Politicality in the Context of the International Olympic Committee’s Functioning - Kobierecki, Michał M. (International Studies. Interdisciplinary Political and Cultural Journal, 2022)
The article discusses the issue of the non-political character of sport. The research aims to trace the position of the International Olympic Committee towards the politicization of sport and to confront it with IOC’s actual activities that can be described as political. The research led to the conclusion that the apolitical character of sport is only a myth. The mass popularity of sport led many states to try to use it for political purposes, forcing the IOC to assume a political position and transferring political disputes to their forum.